Weightlifting: an applied method of technical analysis - Chavda, S.; Hill, M.; Martin, S.; Swisher, A.; Haff, G. G.; Turner, A. N. (Strength and Conditioning Journal, 2021)
Weightlifting is a highly technical sport that is governed by interactions of phases to optimize the load lifted. Given the technicality of the snatch and the clean and jerk, understanding key stable components to identify errors and better prescribe relevant exercises are warranted. The aim of this article is to present an applied method of analysis for coaches that considers the biomechanical underpinnings of optimal technique through stable interactions of the kinetics and kinematics of the lifter and barbell at key phases of the lift. This article will also look to discuss variable components that may differentiate between athletes and therefore provide a foundation in what to identify when coaching weightlifting to optimize load lifted while allowing for individual variances.